2020
DOI: 10.5194/acp-20-3945-2020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of typhoons on atmospheric composition deduced from IAGOS measurements over Taipei

Abstract: Abstract. The research infrastructure IAGOS (In-Service Aircraft for a Global Observing System) equips commercial aircraft with instruments to monitor the composition of the atmosphere during flights around the world. In this article, we use data from two China Airlines aircraft based in Taipei (Taiwan) which provided daily measurements of ozone, carbon monoxide and water vapour throughout the summer of 2016. We present time series, from the surface to the upper troposphere, of ozone, carbon monoxide and relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Moreover, these areas at 850 and 700 hPa generally featured higher O3 mixing ratios as well as lower RH (Fig. S6) than others, which is a sign of possible direct downward O3 transport (Roux et al, 2020;Wang et al, 2020). This part of O3 can notably aggravate near-ground O3 pollution in the PRD.…”
Section: O3 Transport Conditions: Comparison Of Wind Speeds Backwardmentioning
confidence: 85%
“…Moreover, these areas at 850 and 700 hPa generally featured higher O3 mixing ratios as well as lower RH (Fig. S6) than others, which is a sign of possible direct downward O3 transport (Roux et al, 2020;Wang et al, 2020). This part of O3 can notably aggravate near-ground O3 pollution in the PRD.…”
Section: O3 Transport Conditions: Comparison Of Wind Speeds Backwardmentioning
confidence: 85%
“…They additionally detected enhanced NO concentrations in the eye wall area and suggested lightning as a source based on observations reported by Davis et al (1996). Roux et al (2020) found the convective uplift of boundary layer air as well as the inflow of lower stratospheric air to the upper troposphere based on measurements of CO, O 3 and H 2 O during aircraft typhoon observations over Taipei in 2016. In contrast, studies of lightning activity within convective systems over the ocean and in tropical cyclones are predominantly based on satellite data and ground-based observations from the WWLLN (University of Washington, 2020; Abreu et al, 2010;Bürgesser, 2017;Hutchins et al, 2012b;Bucsela et al, 2019) Generally, data from in situ chemical measurements in the upper troposphere are sparse, and to our knowledge, the in situ aircraft observation of deep convection in tropical cyclones accompanied by and in the absence of lightning depending on the stage of development has not been reported before.…”
Section: Introductionmentioning
confidence: 75%
“…O 3 mixing ratios were analyzed by UV absorption and chemiluminescence with the FAIRO instrument (chemiluminescence data with a total uncertainty of 2.5 %; Zahn et al, 2012). CO was measured via quantum cascade laser absorption spectroscopy with an uncertainty of 4.3 % (Schiller et al, 2008). H 2 O 2 mixing ratios were measured via dualenzyme detection (modified Aero-Laser AL2021, Garmisch-Partenkirchen, Germany) with a total measurement uncertainty of 9 % and a detection limit of 15 ppt v (Hottmann et al, 2020).…”
Section: Observationsmentioning
confidence: 99%
“…Therefore, they can potentially perturbate the structure and chemical compositions in the tropopause region, and promote stratospheretroposphere exchanges (STEs). For example, several studies show that typhoons can induce the downward intrusions of ozonerich air (Jiang et al, 2015;Das et al, 2016;Li et al, 2018;Roux et al, 2020). Such intrusions can even reach the ABL and deteriorate air quality there, as in the case of Typhoon Hagibis over southeastern coast of China reported by Jiang et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the occurrences of ozone episodes and the spatiotemporal distribution and property of typhoons, Huang et al (2006) found that when a typhoon is about 700-1000 km from the PRD, the region is already controlled by large-scale subsidence of typhoon and suffers high ozone. Roux et al (2020) stated that typhoons at distances of 500-1000 km offshore provide a favourable environment for active photochemical reactions and hence high ozone episodes. It is also documented that surface ozone concentrations increase over southwestern Taiwan 2 to 4 days before the passage of typhoons (Hung and Lo, 2015).…”
Section: Introductionmentioning
confidence: 99%